CHARACTERISTICS OF URINARY TRACT STONE PATIENTS AT Dr. H. CHASAN BOESOIRIE TERNATE REGIONAL GENERAL HOSPITAL 2021-2023 - Hadiputra, Narendra Agung Rizky; Selomo, Prita Aulia M; Yati, Sri (Universitas Muhammadiyah Ponorogo, 2025)
Urinary tract stones (UTC) are the occurrence of stones in the urinary tract organs. Environmental factors such as daily behavior, excess body weight, eating habits, and lack of fluid intake influence the occurrence of UTC. Hormonal, genetic, and anatomical factors can also play a role in its pathogenesis. The purpose of this study was to determine the characteristics of urinary tract stone patients at Dr. H. Chasan Boesoirie Ternate Regional Hospital. This type of research is descriptive research with a cross-sectional approach research design. The data used are secondary data in the form of medical records of UTC patients in 2021-2023. This study obtained a total sample of 171 people, the distribution of patients was mostly male (67.8%), adult age group (â‰¥19-<45 years) (39.2%), normal body mass index (BMI) (49.1%), high school education (58.5%), and civil servant/military/police/state-owned enterprises/regional-owned enterprises occupation (21.1%). Men are at higher risk of experiencing UTC, allegedly due to the role of hormones. Workload, sweat, and lack of fluids that are common in productive age are risk factors for BSK. Obesity triggers urinary tract stones through increased uric acid, decreased urine pH, inflammation, and oxidative stress. Education level can affect the risk of BSK. Work can be a risk for BSK due to sun exposure to poor lifestyle